Reformulation of Decision Execution and Honorary Council Position of Constitutional Court After Decision Number 604/G/2023/PTUN.JKT - wili utama, Alif; Anna Erliyana (Jurisprudentie : Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2024)
Abstract: This research analyzes the strength of the Decision of the Honorary Council of the Constitutional Court Number 2/MKMK/L/11/2023 and its execution after Decision Number 604/2023/PTUN.JKT questioning the Appointment of Constitutional Judge Suhartoyo in the object of a state administrative dispute in the form of Constitutional Court Decree Number 17 of 2013. This type of research is a doctrinal research that examines literature sources and statutory studies. Furthermore, this paper uses a conceptual approach and comparative approach that combines the concept of legal certainty and comparisons of several countries in terms of seeing a broader prototype of Ethics Institute arrangements comprehensively. After conducting an analysis, it can be concluded that the Decision of the Honorary Council of the Constitutional Court Number 17 of 2013 which contains ethical sanctions for violations of Constitutional Judge Anwar Usman is constrained by legal uncertainty in its execution. This is because there is no mechanism for the dismissal of the Chief Justice of the Constitutional Court after the imposition of ethical sanctions and there is a potential dualism in the ethical enforcement system that can be convoluted. The uncertainty of the execution of the Constitutional Court Honor Council Decision which has the potential to be convoluted with the involvement of the State Administrative Court in adjudicating the Decision a quo should be a reflection to distinguish the authority of law enforcement and ethical enforcement and their scope. This can be encouraged by strengthening the status of the Honorary Council of the Constitutional Court in its position as a Supervisory body as well as the arrangement of the Supreme Advisory Council in the Armenian Constitution. Keywords: Honorary Council of the Constitutional Court, Decision ethics, execution